The Relationship between Self Regulated Learning and Self-Adjustment of New Students who Migrate at Makassar State University - Firdauzy Ahsan, Karunia Mulya; Alwi, M Ahkam (Polteknik Ilmu Pemasyarakatan, 2024)
Students are individuals who are currently in the process of acquiring knowledge and are registered at an institution such as a university, polytechnic or other educational institution. Individuals who have just entered the world of college in their first year are called new students. Status as a new student will certainly provide a significant difference compared to when you were a student. This research aims to determine the relationship between self-regulated learning and the adjustment of new students who have migrated from outside South Sulawesi to study at Makassar State University. The sample in this study consisted of 160 people who were new students in 2023 and were currently migrating to South Sulawesi. Data collection was carried out using two research instruments, namely, the self-regulated learning scale and the self-adjustment scale. Hypothesis testing using product moment correlation analysis. The research results show that there is a positive relationship between self-regulated learning and new students' self-adjustment, r = 0.599 (p = 0.000). The higher the level of self-regulated learning, the higher the student's self-adjustment.